"Mommy-see, mommy-do": perceptions of intergenerational "obesity" transmission among lower-income, higher-weight, rural midwestern American women. Issue 3 (3rd July 2022) - Bombak, Andrea; Robinson, Emma; Hughes, Katherine; Riediger, Natalie; Thomson, Lisa
Abstract: Public health and media discourses frequently blame mothers for the size of their children, including parents coping with multiple structural disadvantages. Rural Midwestern American, low-income, self-identified higher-weight women (n = 25) participated in face-to-face, audio-recorded, semi-structured interviews about their beliefs regarding how body size is transmitted across generations. We analyzed interviews using causation coding. Participants facing socioeconomic and geographic barriers to salutogenic lifestyles de-emphasized genetic and epigenetic factors in body size. Instead, participants focused on parents' role modeling, provision of "obesogenic" foods, and failure to enact protective behaviors like providing non-"obesogenic" foods and limiting children's screen time. Findings demonstrate that the moralization of childhood "obesity" is pervasive, and these damaging discourses have been taken up among those facing socioeconomic disadvantage.